Stem cells and lower urinary tract dysfunction: Has its potential finally reached clinical maturity? ICI‐RS2018. (10th December 2019) - Chermansky, Christopher; Mitsogiannis, Iraklis; Abrams, Paul; Apostolidis, Apostolos
Abstract: Aims: Efforts to engineer and repair genitourinary tissue to treat lower urinary tract dysfunction (LUTD) have recently increased thanks in part to advances in stem cell (SC) research. At the International Consultation on Incontinence‐Research Society meeting in Bristol in 2018 a proposal was convened to address the question: has the potential of SCs in treating LUTD reached clinical maturity? Methods: The proposal conducted a literature review and an expert consensus meeting focusing on available data from animal models and clinical trials involving the use of SCs for LUTD. Results: To date, there are only small studies investigating bladder replacement using scaffolds with or without SC. Results have been conflicting because of the variability in cell numbers, biomaterials types, and graft surface differences. Similarly, preclinical results suggest a possible role of SC in bladder outlet obstruction (BOO); however, SC clinical trials for BOO are lacking. Research into the use of SC for female stress urinary incontinence (SUI) is close to reaching clinical maturity. In the Canadian phase 3 randomized controlled trial (RCT), a beneficial effect of adult muscle–derived cells (AMDC) over placebo was detected in reducing the frequency of incontinence episodes, especially after prior anti‐incontinence surgery. Only two small studies have been published on male SUI. Conclusions: Questions remain regarding the mechanism of action of SC injected into the LUT and the viability of cells seeded onto grafts placed into the LUT. Also, the optimal time for intervention with SC therapy in the LUT remains to be elucidated.